2018
DOI: 10.18632/oncotarget.25550
|View full text |Cite
|
Sign up to set email alerts
|

Trends and outcomes of women with synchronous endometrial and ovarian cancer

Abstract: This retrospective observational study examined trends, characteristics, and survival of women with synchronous endometrial and ovarian cancer (SEOC) in the Surveillance, Epidemiology, and End Results Program between 1973 and 2013. Among 235,454 women with primary endometrial cancer, synchronous ovarian cancer was seen in 4,082 (1.7%) women with the proportion being decreased from 2.0% to 1.6% between 1983 and 2013 (P=0.049); and the proportion of concurrent endometrioid tumors in the two cancer sites has incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 31 publications
2
36
0
2
Order By: Relevance
“…Most common histological combination was endometrioid cancer in both ovary and uterus (45.6%) followed by endometrioid cancer in uterus and non-endometrioid cancer in ovary (33%) and non-endometrioid cancer in both ovary and uterus (16.1%). Women with synchronous endometrioid cancer in both ovary and uterus were younger and had better 10 year survival rate (88.7%) compared to women with endometrioid carcinoma of uterus and non-endometrioid cancer of ovary (74.2%), non endometrioid cancer in both ovary and uterus (62.9%) and women with only endometrial carcinoma (80.7%) [5]. In another study [6], 3.3% of women with endometrial cancer and 2.7% of women with cancer of ovary had evidence of synchronous cancer of ovary or uterus respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most common histological combination was endometrioid cancer in both ovary and uterus (45.6%) followed by endometrioid cancer in uterus and non-endometrioid cancer in ovary (33%) and non-endometrioid cancer in both ovary and uterus (16.1%). Women with synchronous endometrioid cancer in both ovary and uterus were younger and had better 10 year survival rate (88.7%) compared to women with endometrioid carcinoma of uterus and non-endometrioid cancer of ovary (74.2%), non endometrioid cancer in both ovary and uterus (62.9%) and women with only endometrial carcinoma (80.7%) [5]. In another study [6], 3.3% of women with endometrial cancer and 2.7% of women with cancer of ovary had evidence of synchronous cancer of ovary or uterus respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In one landmark study [5] (n=235,454 women with endometrial carcinoma), synchronous ovarian cancer was found in 1.7% of women with endometrial carcinoma, the incidence being highest (3.1-5%) in women between 29-47 years of age. The women with synchronous endometrial carcinoma and ovarian cancer were more often young black women with grade 1-2 tumors of endometrioid or serous histology type and stage I-II disease [5]. Most common histological combination was endometrioid cancer in both ovary and uterus (45.6%) followed by endometrioid cancer in uterus and non-endometrioid cancer in ovary (33%) and non-endometrioid cancer in both ovary and uterus (16.1%).…”
Section: Discussionmentioning
confidence: 99%
“…SEOC is the simultaneous occurrence of both endometrial and ovarian cancers at the time of diagnosis. 6 Although a rare instance, SEOC is the most frequent of the synchronous female genital tract cancers, 2,7,12 which accounts for 0.7 to 1.8% of all gynecologic malignancies. 2 SEOCs occur in younger women than those with either of primary ovarian or primary endometrial malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…2 SEOCs occur in younger women than those with either of primary ovarian or primary endometrial malignancies. 5,6 A population-based retrospective analysis of SEOCs by Matsuo et al showed that among the endometrial cancer cohorts, synchronous primary endometrioid endometrial and ovarian tumors accounted for majority of the cases; while synchronous primary nonendometrioid ovarian and endometrial tumors accounted for only 16% of the cases, 21.8% accounted for the high-grade (grades 2 and 3) tumors. 6 In their study, grade 3 synchronous primary nonendometrioid ovarian and endometrial carcinomas to which group the index case belongs, accounted for only 5% of the SEOCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation